Study on adsorption and desorption of phenoxycarbonic acids on silica surface - Smirnova, O. V (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2007)
Adsorption of lines phenolic connections with various functional groups on a silica surface is investigated. The contribution of waterproof interaction and formation of hydrogen bonds with carboxyl and hydroxyl protons in adsorption’s process is determined. By temperature-programmed desorption mass spectrometry was determines dependence of thermal stability phenolic connections from a structure of molecules and adsorption on silica. The method of a nuclear magnetic resonance of the high sanction in conditions frosting a liquid phase establishes dependence of superficial energy ｧs, on a structure of the present molecules phenolic connections. Therefore, one can distinguish two types of interaction of phenolic connections with silicon dioxide surface: specific interaction with surface silanol groups and nonspecific interaction with carbohydrate component of methyl-silica surfaces.